Lead detection using a pineapple bioelectrode - Mojica, Elmer-Rico E.; Gomez, Socrates P.; Micor, Jose Rene L.; Deocaris, Custer C. (2006)
Freeze dried pineapple fruit peelings were powderized and used as a modifier of a carbon paste electrode. The pineapple bioelectrode was used to determine trace levels of lead in aqueous solution. Accumulation was followed by medium-exchange to an electrolyte solution where surface bound lead ions were measured. The response of the modified electrodes was assessed in terms of the supporting electrolyte used, proportion of the pineapple in the bioelectrode, pH, accumulation time, deposition time, deposition potential, regeneration and lead concentration. The surface was successfully renewed by soaking the electrode in an EDTA solution. The relative standard deviation for ten accumulation/measurement/renewal cycles with a 1 mg L-1 lead ion solution was 4.2%. The peak current was directly proportional to the concentration of lead ions in the range of 1-10 mgL-1 (R=0.991). The presence of other metals such as Cr(III), Cd(II), Zn(II), Co(II), Ni(II), Ca(II), Mg(II), Mn(II), AI(II) and Fe(III) did not interfere with the determination of Pb(II) although Hg(II), Ag(I) and Cu(II) reduced the peak of Pb(II) by 11.82-34.61%. The pineapple bioelectrode was successfully used to measure the lead content of lead-spiked water and a laboratory waste sample with values very similar to those obtained by atomic absorption spectrometer.
Keywords: Lead; Pineapple